Kinetic simulations of mildly relativistic shocks – I. Particle acceleration in high Mach number shocks. Issue 4 (30th January 2019) - Crumley, P; Caprioli, D; Markoff, S; Spitkovsky, A
Abstract: We use fully kinetic particle-in-cell simulations with unprecedentedly large transverse box sizes to study particle acceleration in weakly magnetized mildly relativistic shocks travelling at a velocity ≈ 0.75 c and a Mach number of 15. We examine both subluminal (quasi-parallel) and superluminal (quasi-perpendicular) magnetic field orientations. We find that quasi-parallel shocks are mediated by a filamentary non-resonant (Bell) instability driven by returning ions, producing magnetic fluctuations on scales comparable to the ion gyroradius. In quasi-parallel shocks, both electrons and ions are accelerated into non-thermal power laws whose maximum energy grows linearly with time. The upstream heating of electrons is small, and the two species enter the shock front in rough thermal equilibrium. The shock's structure is complex; the current of returning non-thermal ions evacuates cavities in the upstream that form filaments of amplified magnetic fields once advected downstream. At late times, 10 per cent of the shock's energy goes into non-thermal protons and ${\gtrsim }10{{\ \rm per\ cent}}$ into magnetic fields. We find that properly capturing the magnetic turbulence driven by the non-thermal ions is important for properly measuring the energy fraction of non-thermal electrons, εe . We find εe ∼ 5 × 10 −4 for quasi-parallel shocks with v  = 0.75 c, slightly larger than what was measured in simulations of non-relativistic shocks. In quasi-perpendicular shocks, no non-thermal power-law develops in ions or electrons. The ion acceleration efficiency in quasi-parallel shocks suggests that astrophysical objects that could host mildly relativistic quasi-parallel shocks – for example, the jets of active galactic nuclei or microquasars – may be important sources of cosmic rays and their secondaries, such as gamma-rays and neutrinos.